2016
DOI: 10.1158/1078-0432.ccr-15-2380
|View full text |Cite
|
Sign up to set email alerts
|

FBW7 (F-box and WD Repeat Domain-Containing 7) Negatively Regulates Glucose Metabolism by Targeting the c-Myc/TXNIP (Thioredoxin-Binding Protein) Axis in Pancreatic Cancer

Abstract: Purpose: FBW7 functions as a tumor suppressor by targeting oncoproteins for destruction. We previously reported that the oncogenic mutation of KRAS inhibits the tumor suppressor FBW7 via the Ras-Raf-MEK-ERK pathway, which facilitates the proliferation and survival of pancreatic cancer cells. However, the underlying mechanism by which FBW7 suppresses pancreatic cancer remains unexplored. Here, we sought to elucidate the function of FBW7 in pancreatic cancer glucose metabolism and malignancy.Experimental Design:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 40 publications
2
58
0
Order By: Relevance
“…Mounting evidence has pointed out c-Myc to be a Kras target (41). Moreover, we also reported that in pancreatic cancer, Kras mutation activated ERK, leading to destabilization of tumor suppressor FBW7, which ultimately led to c-Myc upregulation (24). These observations prompted us to consider MUC16 as a c-Myc downstream transcriptional target.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Mounting evidence has pointed out c-Myc to be a Kras target (41). Moreover, we also reported that in pancreatic cancer, Kras mutation activated ERK, leading to destabilization of tumor suppressor FBW7, which ultimately led to c-Myc upregulation (24). These observations prompted us to consider MUC16 as a c-Myc downstream transcriptional target.…”
Section: Discussionmentioning
confidence: 83%
“…iKras cell lines, which express Kras G12D upon doxycycline (doxy) treatment, and human pancreatic nonmalignant epithelial HPNE cells were generously provided by Professor Paul J. Chiao. PANC-1 and SW1990 cell lines with FBW7 overexpression were generated previously (24).…”
Section: Cell Culturementioning
confidence: 99%
“…Total RNA was extracted with TRIzol reagent (Invitrogen), purified using the PureLink RNA Minikit (Life Technologies), and assessed for quality and quantity using absorption measurements. The expression of candidate genes and b-actin was determined by quantitative real-time PCR, according to the standard procedures described previously (9). RNA was used for analysis of Human Oxidative Stress using pathway-focused RT-PCR array systems (The Human Oxidative Stress RT 2 Profiler PCR Array; PAHS-065ZA; Qiagen).…”
Section: Qpcr Analysismentioning
confidence: 99%
“…Accumulated evidence has demonstrated that metabolic reprogramming is an emerging hallmark of cancer (8). Our previous findings indicated that ERK kinase modulates F-box and WD repeat domain-containing 7 (FBW7) ubiquitination in a T205 phosphorylation-dependent manner, and FBW7 is a negative regulator of mitochondrial respiration in pancreatic cancer cells, thereby revealing an important function of Kras/ERK/FBW7 axis in promoting PDAC progression (7,9). However, the mechanism underlying the impact of ERK/FBW7 on mitochondrial metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, it was recently reported that FBW7 targets CDX2 (caudal-related homeobox transcription factor 2) for degradation via two cdc42-phosphoclegron motifs in a GSK3beta-dependent manner[52]. Ji et al[53] have recently reported that KRAS mutations inhibit the tumor suppressor FBW7, which negatively regulates glucose metabolism by targeting the c-Myc/TXNIP (thioredoxin binding protein) axis in pancreatic cancer. The expression level of FBW7 was negatively associated with PET/CT SUVmax in 60 pancreatic cancer patients, indicating that FBW7 is an important KRAS downstream effector and might reverse KRAS-driven metabolic change.…”
Section: F-box and Wd Repeat Domain-containingmentioning
confidence: 99%